DIGITAGRO - Investing in Digital Technology to Increase Market Access for Women Agri-preneurs in Guatemala - Perego, Viviana M.E.; Romero, Javier; Freeman, Katie; Lopez, Angela; Ortiz, Glenn; Salas, Hugo; Ramirez, Rudy; Locatelli, Arianna; Orihuela, Danielle; de Ferrari, Camila (Washington, DC: World Bank, 2022)
Despite the strong role played by the agri-food sector in Guatemala’s economic performance and employment, reflected in high exports and strong results by larger commercial agri-businesses, small producers face daunting levels of market access, revenue generation capacity, and resilience. Schools in remote areas, however, often lack information on which producer to buy their food from, as well as basic knowledge on safe and hygienic cooking practices. These challenges are further exacerbated for women producers, who face higher information gaps, lower market access, and higher informality than their male counterparts, compounded by restrictive social norms and disempowerment. Yet, women who are engaged in agriculture have ample potential to be engaged in the school feeding business, as they tend to specialize in the production of foods that are in high demand by school. The School Feeding Program (SFP) thus represents a crucial window of opportunity for rural women in Guatemala, and a vehicle for their evolution from invisible farmers to proper agri-preneurs – economic agents in their own right in the agribusiness space. Information diffusion through digital technologies can increase market participation in rural areas and holds promise to enhance the status of women in the business sphere. The World Bank’s DIGITAGRO project, piloted digital technologies to improve market access for women agripreneurs, so they could supply the School Feeding Program in a fair, safe, sustainable, and profitable way while helping schools improve children’s nutrition. The purpose of this report is to describe the DIGITAGRO project and to present the findings of the impact evaluation study on the information campaign, in order to derive lessons on the use of digital technologies to promote market access for rural women, with a specific focus on their inclusion in Guatemala’s School Feeding Program The rest of the report is organized as follows. Chapter 2 provides an overview of family farming in Guatemala, including an assessment of the gaps encountered by rural women, and highlights child nutrition issues in the country. Chapter 3 describes the School Feeding Program, highlighting its functioning, the main actors involved, its expected benefits and the challenges it faces. Chapter 4 presents the DIGITAGRO project, providing a rationale for the use of digital technologies in agriculture, describing the main activities of the project, and providing details on the set-up of the impact evaluation study. Chapter 5 presents the experimental setting and main findings of the impact evaluation, whereas the potential mechanisms that could be driving the results are explored in Chapter 6, together with recommendations for promoting participation in the School Feeding Program. Chapter 7 discusses lessons learned and concludes.